2023
DOI: 10.3390/soilsystems7010018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Tissues of Syringa vulgaris L. and Soil Features in Abandoned Cemeteries

Abstract: Abandoned anthropogenic sites are transformed when they come into use. In the present study, such objects were abandoned Evangelical cemeteries located in the Land of the Great Mazurian Lakes (northern Poland). This study aims to compare the concentrations of selected major (Ca, Na, Mg, Al, Fe) and potentially toxic elements (Zn, Cd, Pb) in the roots, leaves, and branches of Syringa vulgaris and buried necrosols and unburied soils in which this species grows. The soils analysed differ in their profile structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…A return to conditions prior to regulation and human influence is an impossible ideal that those undertaking revitalization efforts are striving for, because the current state is the result of a whole range of human activities that have lasted for millennia [26,27]. The results relate to studies conducted in other regions of Poland indicating the impact of anthropopressure on species diversity resulting from the formation of habitat complexes [20,29,46]. In the regulated section of the Odra, an initial ecosystem was highly disturbed by meander cut offs and mining activity at the floodplain.…”
Section: Discussionmentioning
confidence: 84%
“…A return to conditions prior to regulation and human influence is an impossible ideal that those undertaking revitalization efforts are striving for, because the current state is the result of a whole range of human activities that have lasted for millennia [26,27]. The results relate to studies conducted in other regions of Poland indicating the impact of anthropopressure on species diversity resulting from the formation of habitat complexes [20,29,46]. In the regulated section of the Odra, an initial ecosystem was highly disturbed by meander cut offs and mining activity at the floodplain.…”
Section: Discussionmentioning
confidence: 84%
“…The release rate constant and correlation coefficient showed the best results, N (kN), and C/N ratio. The chemical composition of the plant residue, namely the concentration of N-organics, C-organics, C/N ratio, lignin, polyphenols, lignin/N ratio, polyphenol/N ratio, and (lignin + polyphenol)/N ratio, determines the rate of N mineralization (Kaleeem Abbasi et al, 2015;Rahmonov et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…A significant difference was detected in the amount of N minerals released in the various compositions of peanut and straw residue mixtures. Based on the results of using wheat straw with two types of moisture content (dry and wet), Rahmonov et al (2023) showed that the morphology of plant tissue (small diameter of the stem and the thickness of the thin wall of the stem) determines the differences in the structure of organic matter's/rice straw composition (total C, total N, hemicellulose, cellulose, and lignin) and ultimately determines the amount of decomposition under the same environmental conditions, namely moisture content.…”
Section: Discussionmentioning
confidence: 99%
“…Its broad ecological valence is also cited in the literature. It is even said to be a typical species of forest gaps formed after fires, snow damage, and blowdowns [54,64].…”
Section: Discussionmentioning
confidence: 99%